IELTS Preparation and Practice : Listening and Speaking - Sahanaya, Wendy and Lindeck, Jeremy (Australia Oxford University Press, 2008)
A series providing comprehensive preparation for the IELTS. With Practice Tests with annotated key.
Include Graph Tables
Keywords: English language -- a